WEBGIS-BASED TOURISM POTENTIAL MAPPING USING QUANTUM GIS (QGIS) - Maymuna, Natasya; Utomowati, Rahning; Noviani, Rita; Ismail, Hairul Nizam bin (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Currently, technology plays an important role in the digital information era. Digital mapping based on WebGIS is one form of Geographic Information System technological output that can impact the development of the tourism sector. The limitation of information sources on tourist attractions is one of the obstacles to tourism development in Indonesia. Therefore, the presence of WebGIS-based tourist attraction mapping can increase the availability of digital information that can impact increasing tourist visits. This research aims to analyze the potential of tourist attractions, perform WebGIS-based mapping of tourist attractions, and analyze the strategies for developing the potential of tourist attractions in Dukuh Village. This research is conducted using a qualitative descriptive method with a geographical spatial approach. The sampling techniques used are saturated sampling to determine tourist attraction samples, purposive sampling to select informants, and accidental sampling to determine tourist samples. The analysis techniques in this study include scoring analysis and Geographic Information System. The research results indicate that there are 16 tourist attractions, consisting of 8 very potential, 6 quite potential, and 2 less potential. Based on these results, WebGIS-based mapping of tourist attractions was performed and tested by 3 media experts. The testing results show that WebGIS media has a good level of effectiveness to be used as one of the media for information and promotion of tourist attractions in Dukuh Village. To support the development of tourist attractions, strategies for developing tourist attractions were formulated and categorized into growth, diversification, and conservative strategies.